1992
DOI: 10.1007/bf00172707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucocorticoid and chemotherapy on the peritumoral edema and astrocytic reaction in experimental brain tumor

Abstract: To study the effects of glucocorticoids and chemotherapeutic agents on the pathophysiology of the tumor-induced brain edema, the site of Evans blue-albumin extravasation, the distribution of extravasated serum albumin, and the extent of local astrocytic reaction were examined in a rat model of implanted brain tumor. Experimental brain tumors were produced by implanting small pellets of Walker 256 carcinosarcoma into the cerebral cortex of Wistar rats. In the steroid group, rats were administered with intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…Previous studies with various exogenous tracers have failed to show any change in BBB permeability [3,5,13,14,18]. No leakage of trypan blue was detected in the monkey brain, even after an irradiation with 60 Gy [5].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Previous studies with various exogenous tracers have failed to show any change in BBB permeability [3,5,13,14,18]. No leakage of trypan blue was detected in the monkey brain, even after an irradiation with 60 Gy [5].…”
Section: Discussionmentioning
confidence: 54%
“…Although increased BBB permeability soon after irradiation has not been documented by previous reports [3,5,13,14,18], an electron microscopic study has demonstrated ultrastructural evidence for increased BBB permeability [4]. As early as 6 hours after irradiation with 27 Gy, pinocytotic vesicles were increased in number in the vascular endothelium of monkey brain.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…All animals were sacrificed at this time point with 100% of animals showing evidence of tumour burden upon histological analysis. Walker 256 implantation models of secondary brain tumours have been described previously in the literature Jamshidi et al, 1992;Morreale et al, 1993). However tumours in the current study grew quicker than those reported previously.…”
Section: Resultscontrasting
confidence: 38%